Sulfonic acid–functionalized Wang resin (Wang-OSO3H) as polymeric acidic catalyst for the ecofriendly multicomponent synthesis of polyhydroquinolines via Hantzsch condensation. Issue 18 (16th September 2016) - Dhanunjaya Rao, A. V.; Surasani, Rajendra; Vykunteswararao, B. P.; Bhaskarkumar, T.; Srikanth, B.; Jogdand, Nivrutti R.; Kalita, Dipak; Lilakar, Jaydeep Kumar D.; Siddaiah, Vidavalur; Sanasi, Paul Douglas; Raghunadh, Akula
ABSTRACT: An efficient and green approach has been developed for the synthesis of polyhydroquinoline derivatives via Hantzsch condensation reaction directly from corresponding substituted aromatic and aliphatic aldehydes, β -keto compounds, active methylene compounds, and ammonium chloride using recyclable polymer-supported sulfonic acid catalyst under aqueous conditions. Environmental acceptability, operational simplicity, low cost, excellent functional group compatibility, and high yields are the important features of this protocol. GRAPHICAL ABSTRACT: